Gender composition of editorial boards in Pakistani Medline-indexed journals: a disaggregated analysis - Masood Ali Shaikh; Syed Muhammad Mubeen (Journal of the Pakistan Medical Association, 2026)
Editorial boards determine the direction and scope of journals. The objective of this study was to assess the gender composition of the editorial boards of four Pakistani Medline-indexed journals using a descriptive cross-sectional study design. Gender composition of the editorial boards of four Pakistani Medline-indexed journals was assessed using a descriptive cross-sectional study design. The publicly available official editorial board pages were accessed and analysed for: Journal of the Pakistan Medical Association (JPMA), Journal of Ayub Medical College (JAMC), Journal of the College of Physicians and Surgeons of Pakistan (JCPSP), and Pakistan Journal of Pharmaceutical Sciences (PJPS). Cumulatively, 163 individuals comprised the editorial boards in these journals, out of which 112 (68.7%) were males. JPMA had the largest editorial team with 59 individuals, and JCPSP had the smallest team with 25 individuals. The most and least gender-diverse editorial teams were reported by JPMA and JAMC, with 22 (37.3%) and 6 (20.7%) women, respectively. Results augur the need for gender-sensitive training programmes to promote gender balance in the editorial boards of the country’s medical journals. Key words: Medical Journals, Editorial boards, Gender equity, Women, Pakistan.